TERRORISM AS A CHANNEL OF TRANSLATION OF INTERESTS OF SHADOW SUBJECTS IN POLICY IN THE CONDITIONS OF A GEOSTTRATEGY OF A UNEVEN DEVELOPMENT OF THE WORLD SOCIETY - D. K. Khalkechev (Современная наука и инновации)
The collapse of the USSR became a powerful detonator of global changes: the end of the bipolar configuration of geopolitical forces, the fall of the Berlin wall, which put an end to the rigid division of the world into two opposing camps, coincided with the beginning of qualitative changes not only in the geostrategic structure that developed in the postwar decades, but also in the most Eurocentric (or rather, euroamericanocentric) world order of the New and Modern times.